Surface-circulation change in the southwest Pacific Ocean across the Middle Eocene Climatic Optimum: inferences from dinoflagellate cysts and biomarker paleothermometry - M. J. Cramwinckel; L. Woelders; E. P. Huurdeman; F. Peterse; S. J. Gallagher; J. Pross; C. E. Burgess; G.-J. Reichart; A. Sluijs; P. K. Bijl (Climate of the Past, 2020)
Global climate cooled from the early Eocene hothouse ( ∼52 –50 Ma ) to the latest Eocene ( ∼34 Ma ). At the same time, the tectonic evolution of the Southern Ocean was characterized by the opening and deepening of circum-Antarctic gateways, which affected both surface- and deep-ocean circulation. The Tasmanian Gateway played a key role in regulating ocean throughflow between Australia and Antarctica. Southern Ocean surface currents through and around the Tasmanian Gateway have left recognizable tracers in the spatiotemporal distribution of plankton fossils, including organic-walled dinoflagellate cysts. This spatiotemporal distribution depends on both the physicochemical properties of the water masses and the path of surface-ocean currents. The extent to which climate and tectonics have influenced the distribution and composition of surface currents and thus fossil assemblages has, however, remained unclear. In particular, the contribution of climate change to oceanographic changes, superimposed on long-term and gradual changes induced by tectonics, is still poorly understood. To disentangle the effects of tectonism and climate in the southwest Pacific Ocean, we target a climatic deviation from the long-term Eocene cooling trend: the Middle Eocene Climatic Optimum (MECO; ∼40 Ma ). This 500 kyr phase of global warming was unrelated to regional tectonism, and thus provides a test case to investigate the ocean's physicochemical response to climate change alone. We reconstruct changes in surface-water circulation and temperature in and around the Tasmanian Gateway during the MECO through new palynological and organic geochemical records from the central Tasmanian Gateway (Ocean Drilling Program Site 1170), the Otway Basin (southeastern Australia), and the Hampden Beach section (New Zealand). Our results confirm that dinocyst communities track specific surface-ocean currents, yet the variability within the communities can be driven by superimposed temperature change. Together with published results from the east of ...